Progress in the study of autophagy-related proteins affecting resistance to chemotherapeutic drugs in leukemia - Li, Meng; Li, Jing; Zhang, Shiming; Zhou, Linghan; Zhu, Yuanyuan; Li, Shen; Li, Qiong; Wang, Junjie; Song, Ruipeng (Frontiers in Cell and Developmental Biology, 2024)
Leukemia is a life-threatening malignant tumor of the hematopoietic system. Currently, the main treatment modalities are chemotherapy and hematopoietic stem cell transplantation. However, increased drug resistance due to decreased sensitivity of leukemia cells to chemotherapeutic drugs presents a major challenge in current treatments. Autophagy-associated proteins involved in autophagy initiation have now been shown to be involved in the development of various types of leukemia cells and are associated with drug resistance. Therefore, this review will explore the roles of autophagy-related proteins involved in four key autophagic processes: induction of autophagy and phagophore formation, phagophore extension, and autophagosome formation, on the development of various types of leukemias as well as drug resistance. Autophagy may become a promising therapeutic target for treating leukemia.